Freight consolidation as a coordination mechanism in perishable supply chains: A simulation study (2015)
One of the most demanding needs of the primary sector is the development of methods, tools, models and techniques for the accurate and efficient management of perishables along the Supply Chain (SC), particularly focused on advanced logistics services (Third-Party Logistics 3PL) such as freight consolidation. This coordination strategy looks for the alignment of agents and processes around the efficient freight handling by minimizing costs and allowing the proper use of transportation capacity resources. The contribution of this paper relies on the analysis of benefits regarding freight consolidation strategies in the context of Agricultural Supply Chains (ASC) by using a simulation approach. The results of a discrete-event simulation with one commodity product evaluated in three different scenarios prove the benefits of this coordination strategy by reducing the number of annual shipments from 1732 to 725 in a city logistics context and increasing fleet utilization levels up to 71%.